Efektivitas Leaflet Menu PMT dalam Meningkatkan Pengetahuan Ibu terhadap Pencegahan Stunting di Kelurahan Jurang, Temanggung - Muhammad Rian Setyawan; Tito Yasin Hidayah; Naufal Ainun Ridho Wibowo; Dewi Setyaningrum; Nabila Exsa Tristanti; Siti Yurika Kurniawati; Devita Putri; M Rayhan Fadhil Rais; Kartika Sekar Damayanti; Muhamad Rizal Rifa’i; Budi Hartono (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting remains a chronic nutritional issue and a significant public health challenge in Indonesia, particularly in rural areas such as Jurang Village, Temanggung Regency. One of the key contributing factors to the high prevalence of stunting is the low level of maternal knowledge regarding balanced nutrition and the appropriate practice of providing supplementary feeding (Pemberian Makanan Tambahan or PMT) for children under five. This study aims to evaluate the effectiveness of PMT menu leaflet media as a tool to increase mothers’ knowledge and awareness regarding stunting prevention. The research was conducted through a series of community-based surveys during Posyandu (integrated health post) activities across several neighborhood units (Rukun Warga or RW). These surveys identified cases of stunting and assessed the educational needs of mothers with young children. Based on the findings, a culturally and contextually adapted leaflet was developed, containing essential information about stunting, its early signs, the importance of PMT, and practical, nutritious recipes made from locally available ingredients. To expand accessibility, the leaflet also included a QR code linked to a digital e-book featuring 54 variations of PMT menus. The educational materials were distributed through door-to-door visits, accompanied by the direct provision of supplementary food, enabling immediate practice of the knowledge shared. Post-intervention results showed a significant improvement in maternal understanding of stunting and nutrition, as well as positive feedback regarding the clarity, relevance, and usefulness of the leaflet. The culturally tailored approach and integration of digital resources further enhanced engagement and knowledge retention. In conclusion, the PMT leaflet proved to be an effective, practical, low-cost, and replicable educational intervention to support community-based stunting prevention efforts in Jurang Village. This approach offers a promising model for similar rural areas facing high stunting rates across Indonesia.